(untitled) (Revista de Estudios Europeos, 2026)
This article examines Greenland’s strategic role within the context of the growing geopolitical competition between the European Union and China in the Arctic. Drawing on a review of the island’s legal and political evolution, it critically analyzes the positions of both actors, with particular attention to the interests, instruments, and models of engagement each deploys. The study offers a comparative evaluation of the opportunities and challenges that this competition generates for Greenland’s development, autonomy, and international projection. Far from being a mere passive arena for external projection, the island is emerging as a developing actor whose decisions and institutional capacities are crucial to managing the effects of this competition within its territory.